Oestrogen receptors and the response to endocrine therapy in advanced breast cancer. - Roberts, M. M. (Nature Publishing Group, 1978)
The relationship between oestrogen-receptor protein (ER) content of the tumour and the response to endocrine therapy was determined in 119 patients, in a collaborative prospective study. Twenty-eight of the 80 patients with measurable ER responded to treatment according to UICC criteria, compared with only 3/39 without ER. It was found that site of biopsy did not influence the result, but tumour content of the tissue sample was significantly related to the presence of receptors. The organizational problems of such a study are discussed.